1971
DOI: 10.2135/cropsci1971.0011183x001100030035x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leaf Pubescence on Transpiration, Photosynthetic Rate and Seed Yield of Three Near‐Isogenic Lines of Soybeans1

Abstract: Apparent photosynthesis (AP), transpiration (TR) and seed yield were determined under field conditions for three near-isogenic lines (isolines) of 'Clark' soybeans (Glycine max (L.) Merr.) differing in pubescence. AP of fully expanded leaves near the top of the plant and T R of individual plants were measured during the flowering stage.Seed yields artd AP rates were not affected by pubescence but the dense pubescent isoline had lower transpiration rates than the normal or glabrous isoline.Additional index-word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Suggested reasons for pubescence include (1) reduced leaf transpiration rates (Ghorashy et al 1971); (2) reduced radiation load (Richards 1996); and (3) promoted water condensation (Konrad et al 2014). Reynolds et al (1999) suggested that leaf hairiness could be an important selection target in breeding drought-resistant wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Suggested reasons for pubescence include (1) reduced leaf transpiration rates (Ghorashy et al 1971); (2) reduced radiation load (Richards 1996); and (3) promoted water condensation (Konrad et al 2014). Reynolds et al (1999) suggested that leaf hairiness could be an important selection target in breeding drought-resistant wheat.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several soybean trichome developmental mutants available, including P1 (glabrous), pc (curly pubescence), Pd (dense pubescence), Ps (sparse pubescence), and p2 (puberulent) that are each controlled by a different single Mendelian locus [27]. These mutants have been used to relate the importance of trichome to insect resistance [4,28,29], evapotranspiration [2,30,31] and other yield related characteristics. However, until now, none of these glabrous classical mutations has been studied at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…The principal functions of trichomes include: (1) resistance against herbivories and pathogens by physically interfering with their movement, and by direct toxicity though chemicals (e.g. monoterpenes and sesquiterpenes) produced or released , Tian et al, 2012, (2) protection against UV radiation, maintaining leaf surface temperature and preventing dehydration by increasing reflection, decreasing transpiration and reducing air movement on the leaf surface (Ghorashy et al, 1971, Nielsen et al, 1984, Taheri et al, 2014, (3) secreting secondary metabolites. For examples, glandular trichomes can exude various metabolites that not only repel insects but can also be used by pharmaceutical industry, in pesticides, and as food additives (Glas et al, 2012).…”
Section: Penetration Of Nutrients Through Stomatamentioning
confidence: 99%
“…48, 355-381. Dar, T. A., Uddin, M., Khan, M. M. A., Hakeem, K., Jaleel, H. (2015) Ghorashy, S., Pendleton, J., Bernard, R., Bauer, M. (1971): Effect of leaf pubescence on transpiration, photosynthetic rate and seed yield of three near-isogenic lines of soybeans.…”
Section: Referencesmentioning
confidence: 99%